Path Analysis of the Influence of Nurses Role on Family Caregiver Diabetes Self-Management Capabilities with Empowerment as Intervening Variables in Indonesia - Rondhianto Rondhianto (Journal of Global Pharma Technology, 2020)
Introduction: Nurses have a responsibility to empower the family that is a preventive promotion effort to improve the ability of the family caregiver to manage diabetes. The purpose of this study was to analyze the role of nurses on the ability of family caregivers through family caregiver empowerment. Methods: This study was an analytic observational study with a cross-sectional design. This study was conducted in the Jember Regency, East Java Province of Indonesia, with a sample size of 150 respondents using a multi-stage random sampling technique. The instrument were namely the Role of the Nurse Perception Questionnaire, Psychological Empowerment Scale, and Diabetes Management Self Efficacy Scale. The data analysis used descriptive analysis and inferential analysis with Structural Equation Modeling-Partial Least Square (SEM-PLS). Results: The results showed that nurse's role had a direct effect on family caregiver empowerment by 93.80% (t = 89.558; p = 0.000 <0.005), but did not have a direct effect on the diabetes self-management capabilities (t = 0.508; p = 0,600> 0,005). However, nurse's role has an indirect effect on the diabetes self-management capabilities through family caregiver empowerment of 64.50% (t = 4.036; p = 0,000 <0.005). This path analysis model is fit model and has an accurate predictive relevance to the existing constructor has a relevant ability to predict (SRMR Value = 0.053 <0.8; Q2=0.331 >0). Conclusion: The nurse's role has a direct influence on family caregiver empowerment and has an indirect effect on the diabetes self-management capabilities through family caregiver empowerment. The efforts to empower family caregivers by nurses through enabling, reinforcing, and supporting as a preventive-promotion intervention need to be improved to enhance the ability of family caregivers in type 2 diabetes management.Keywords: Diabetes Self-Management Capabilities; Family Caregiver Empowerment; Nurse's Role; Type 2 diabetes.